Epidemiology and genetic characteristics of coxsackievirus A16 associated with hand-foot-and-mouth disease in Yantai city, China in 2018–2021 - Zhenlu Sun; Ji Wang; Xin Chi; Peihua Niu; Ruiqing Zhang; Qiao Gao; Yong Zhang; Xuejun Ma (Biosafety and Health, 2023)
In 2008, China launched a national surveillance system for hand-foot-and-mouth disease (HFMD). Several million cases of HFMD are reported every year, coxsackievirus A16 (CVA16) was the leading cause of HFMD epidemic in Yantai city, China in recent years, but the information of epidemiology and molecular characterization of CVA16 in Yantai is limited. The aim of this study is to investigate the epidemiological characteristics and pathogenic spectrum of HFMD, and most importantly, the molecular characterization of CVA16 in Yantai from 2018 to 2021. A total of 2,000 clinical samples were collected in Yantai city from 2018 to 2021 and the enterovirus typing was performed using real-time reverse transcriptase–polymerase chain reaction (qRT-PCR). VP1 coding regions of 41 CVA16 isolates were amplified and Sanger sequenced, and phylogenetic analysis was performed. During the study period, HFMD became prevalent from May to August each year. It peaked in June and declined in September. The incidence was highest in children aged 1 to 5 years, while more common in males than females. 1,617 out of 2,000 clinical collection of samples were tested positive for enterovirus. Among them, 614 were identified as CVA16, 45 were enterovirus A71 (EV A17), and 958 were other enterovirus serotypes. All 41 CVA16 strains belonged to the Bla and B1b genotypes. Homology analysis showed that 41 CVA16 isolates shared 83.2%–100% nucleotide and 93.7%–100% amino acid similarity among themselves. The results of this study update molecular epidemiology of CVA16 and provide a reference for HFMD prevention and control.